Correlation Between PaO2/FIO2 and Peripheral Capillary Oxygenation/FIO2 in Burned Children With Smoke Inhalation Injury. Issue 10 (October 2017) - Cambiaso-Daniel, Janos; Voigt, Charles D.; Rivas, Eric; Hundeshagen, Gabriel; Nunez-Lopez, Omar; Kamolz, Lars-Peter; Sljivich, Michaela; Sousse, Linda E.; Herndon, David N.; Suman, Oscar E.; Kinsky, Michael P.; Mlcak, Ronald P.
Abstract : Objectives: Determine whether the peripheral capillary oxygenation/FIO2 ratio correlates with the PaO2 /FIO2 ratio in burned children with smoke inhalation injury, with the goal of understanding if the peripheral capillary oxygenation/FIO2 ratio can serve as a surrogate for the PaO2 /FIO2 ratio for the diagnosis of acute respiratory distress syndrome. Design: Retrospective chart review. Setting: Shriners Hospitals for Children—Galveston. Patients: All burned children with smoke inhalation injury who were admitted from 1996 to 2014 and had simultaneously obtained peripheral capillary oxygenation, FIO2 and PaO2 measurements. Interventions: None. Measurements and Main Results: Two hundred seventy-three patients (63% male, 8 ± 5 yr, 53% ± 24% total body surface area burns) were analyzed. Peripheral capillary oxygenation/FIO2 ratios were divided into four subgroups based on peripheral capillary oxygenation values (⩽ 100%, ⩽ 98%, ⩽ 95%, and ⩽ 92%). Significance was accepted at r 2 greater than 0.81. The r 2 (number of matches) was 0.66 (23, 072) for less than or equal to 100%, 0.87 (18, 932) for less than or equal to 98%, 0.89 (7, 056) for less than or equal to 95%, and 0.93 (4, 229) for less than or equal to 92%. In the subgroup of patients who developed acute respiratory distress syndrome, r 2 was 0.65 (8, 357) for less than or equal to 100%, 0.89 (7, 578) for less than or equal to 98%, 0.89 (4, 115) for less than or equal to 95%, and 0.91 (2, 288) less than or equal to 92%. Conclusions: PaO2 /FIO2 and peripheral capillary oxygenation/FIO2 strongly correlate in burned children with smoke inhalation injury, with a peripheral capillary oxygenation of less than 92% providing the strongest correlation. Thus, peripheral capillary oxygenation/FIO2 ratio may be able to serve as surrogate for PaO2 /FIO2, especially when titrating FIO2 to achieve a peripheral capillary oxygenation of 90–95% (i.e., in the acute respiratory distress syndrome range).